2012
DOI: 10.1038/srep00583
|View full text |Cite|
|
Sign up to set email alerts
|

Revealing the truth about ‘trapped rainbow’ storage of light in metamaterials

Abstract: It was claimed that the incident light can be gradually slowed down and finally trapped in a tapered metamaterial waveguide. Here we show that the energy incident from the input port of the tapered metamaterial waveguide will be totally reflected (instead of being trapped) due to the strong intermodal coupling between the forward and backward modes. The underlying physical mechanism for this strong intermodal-coupling is given. The occurrence of energy reflection is unambiguously proved using several independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 21 publications
4
61
0
Order By: Relevance
“…modes with significantly different optical properties, the HMM waveguide taper constructed by metal and dielectric films can be used to develop practical on-chip optical super absorbers with a tunable absorption band. Compared with previously reported rainbow trapping platforms 6,9,[10][11][12][13][14][15] , the proposed universal HMM waveguide taper design constitute solid state on-chip photonic architectures capable of simultaneous operation over a wide range of wavelengths throughout visible, near-infrared, midinfrared 27 , terahertz (see Section 5 in the supplementary information) and microwave 34 spectral regions, which is not limited by severe theoretical constraints required by previously reported INI, IMI and MIM waveguide tapers 15 . Combined with advanced micro/nanofabrication technologies, this new and robust scheme will make experimental realization of large area on-chip rainbow trapping platforms more achievable, which will pave the way towards on-chip light localization, spectrum splitting 15 and super absorbers 35 , and will impact a broad range of photon-harvesting and energy technologies ranging from photovoltaics 36 , thin-film thermal absorbers/emitters 37 , to plasmon-mediated photocatalysis 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…modes with significantly different optical properties, the HMM waveguide taper constructed by metal and dielectric films can be used to develop practical on-chip optical super absorbers with a tunable absorption band. Compared with previously reported rainbow trapping platforms 6,9,[10][11][12][13][14][15] , the proposed universal HMM waveguide taper design constitute solid state on-chip photonic architectures capable of simultaneous operation over a wide range of wavelengths throughout visible, near-infrared, midinfrared 27 , terahertz (see Section 5 in the supplementary information) and microwave 34 spectral regions, which is not limited by severe theoretical constraints required by previously reported INI, IMI and MIM waveguide tapers 15 . Combined with advanced micro/nanofabrication technologies, this new and robust scheme will make experimental realization of large area on-chip rainbow trapping platforms more achievable, which will pave the way towards on-chip light localization, spectrum splitting 15 and super absorbers 35 , and will impact a broad range of photon-harvesting and energy technologies ranging from photovoltaics 36 , thin-film thermal absorbers/emitters 37 , to plasmon-mediated photocatalysis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…With the ability to produce highly confined and localized optical fields, it is believed that the conventional rules for light-matter interactions need to be re-examined, and new regimes of optical physics are expected. To develop applications based on this intriguing broadband slow light effect, various architectures have been proposed, including surface graded metallic gratings 9,10 , insulator-negative-index-insulator (INI) 6,11 , insulator-metal-insulator (IMI) 12 and metal-insulator-metal (MIM) waveguide tapers [13][14][15] . However, each proposal has its inherent difficulties resulting in the limited experimental realization of the rainbow trapping structures.…”
mentioning
confidence: 99%
“…Therefore, for a waveguide of a certain core width, the slow-wave modes can be excited around a certain wavelength. Though the lossless assumption cannot explain the physics of broadband absorption accurately, the degeneracy points at the dispersion curves of lossless structures can approximately predict the critical width [28,29].…”
Section: Polarization-dependent Absorption In Tapered Strip Arraymentioning
confidence: 99%
“…By scaling down the feature size of the plasmonic graded metallic grating structures, it has been shown that broadband SPs can be trapped by the plasmonic graded structures in visible frequencies [17]. Up to now, different architectures have been developed for efficiently trapping SPs [18][19][20][21] to facilitate applications of the intriguing slow wave behaviors.…”
Section: Introductionmentioning
confidence: 99%